Association between tobacco smoking and prevalence of HIV, tuberculosis, hypertension and diabetes in rural South Africa: a cross-sectional study - Glory Chidumwa; Stephen Olivier; Hloniphile Ngubane; Thando Zulu; Mareca Sithole; Resign Gunda; The Vukuzazi Team; Ronel Sewpaul; Gina Kruse; Nancy A. Rigotti; Willem A. Hanekom; Mark J. Siedner; et al. (BMC, 2024)
Abstract Background South Africa is facing a convergence of communicable diseases (CDs) and non-communicable diseases (NCDs). There are limited data about how tobacco use contributes to the burden of these conditions, especially in rural populations. Methods We analyzed the associations between current tobacco smoking and four important CDs and NCDs in Vukuzazi, a cross-sectional study of individuals aged 15 years and older conducted between 2018-2020 in a demographic surveillance area in KwaZulu-Natal, South Africa. Data on HIV, active tuberculosis (TB), hypertension and diabetes mellitus were collected via direct measurement from participants. Results Of 18,024 participants (68% female, median age 37 years [interquartile range 23-56 years]), 1,301 (7.2%) reported current smoking. Prevalence of HIV infection was similarly high among people who currently smoked (34.6%) and people who had never smoked (33.9%). However, among people living with HIV (PLWH), there was a higher prevalence of detectable viremia in people reporting current smoking compared to people who reported never smoking (28.8% vs. 16.6%; p-value < 0.001). Active TB was more prevalent in people who currently smoked than in people who never smoked (3.1% vs 1.3%, p < 0.001). In contrast, the prevalence of hypertension and diabetes mellitus were lower in people reporting current smoking than in people reporting never smoking (17.1% vs 26.0% (p < 0.001), and 2.5% vs 10.2% (p < 0.001), respectively). In sex-stratified multiple logistic regression analyses that were adjusted for potential confounding factors (including body mass index for the NCDs), the magnitude of differences in CD prevalence between people who currently smoked and people who never smoked decreased, whereas the lower prevalence of NCDs among people reporting current smoking persisted. Conclusions In rural South Africa, smoking is associated with higher prevalence of active TB, and people with HIV who smoke have worse disease control. In contrast, hypertension and diabetes mellitus are less common in those who smoke. Interventions to screen for TB among those who smoke and to address smoking among people with HIV may be particularly impactful.